Hamiltonian structure of multi component integrable systems - Yazici, D; Oguz, O; Oguz, O (INST PHYSICS ACAD SCI CZECH REPUBLIC, 2001)
In this work we have generalized the super KdV equation into a multicomponent super KdV equation. It is shown that the system is bi-super Hamiltonian. The third super Hamiltonian in the multicomponent super KdV hierarchy is obtained and the corresponding first and second members of evolution equations are given.
Keywords: Physics